1983
DOI: 10.1084/jem.158.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of immune suppression by ultraviolet irradiation in vivo. I. Evidence for the existence of a unique photoreceptor in skin and its role in photoimmunology.

Abstract: UV irradiation of mice causes a systemic immune alteration that can be detected either by suppression of the immunologic rejection of UV-induced tumors, or by suppression of contact hypersensitivity (CHS). Suppression of these two immunologic responses has similar photobiologic characteristics and in both cases is associated with the generation of antigen-specific suppressor T cells. To identify whether a specific photoreceptor for this effect exists, the relative wavelength effectiveness (action spectrum) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
278
0
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 509 publications
(286 citation statements)
references
References 36 publications
7
278
0
1
Order By: Relevance
“…The current studies have shown that UV irradiation may be usefui not oniy for pretreatment of donor tissue but also for immune suppression of graft recipients. UV radiation-induced immunosuppression in vivo is initiated by an interaction between UV and a superficial photoreceptor in skin, tentatively identified as urocanic acid, which photoisomerizes on UV irradiation (26). Recent supportive evidence for this hypothesis has been pre-scntcd indicating that systemic administration of the UV-irradiated form of urocanic acid can initiate, in the absence of UV suppression of a DTH response (27) and the formation of an antigen-presenting cell defect in dendritic antigen presenting cells ofthe spleen (19).…”
Section: Discussionmentioning
confidence: 99%
“…The current studies have shown that UV irradiation may be usefui not oniy for pretreatment of donor tissue but also for immune suppression of graft recipients. UV radiation-induced immunosuppression in vivo is initiated by an interaction between UV and a superficial photoreceptor in skin, tentatively identified as urocanic acid, which photoisomerizes on UV irradiation (26). Recent supportive evidence for this hypothesis has been pre-scntcd indicating that systemic administration of the UV-irradiated form of urocanic acid can initiate, in the absence of UV suppression of a DTH response (27) and the formation of an antigen-presenting cell defect in dendritic antigen presenting cells ofthe spleen (19).…”
Section: Discussionmentioning
confidence: 99%
“…As can be seen in Figure 6, P2X 7 receptor signaling is not required for UV-induced IL-33 in the skin because both groups of mice showed an increase in IL-33 expression. A number of other soluble factors are released within the skin after exposure to inflammatory doses of UV, including cis-urocanic acid (cis-UCA) 52 and the oxidized membrane lipid PAF. 53 To determine whether cis-UCA ( Figure 6F) or PAF ( Figure 6G) could directly induce IL-33 expression in fibroblasts, we incubated MEFs with each of these factors for 1 hour or 4 hours.…”
Section: Uvb and Paf Induce Il-33 Expression In Skinmentioning
confidence: 99%
“…UCA has been suggested as the photoreceptor in the UVR-induced immunosuppressive process (6), and several papers have demonstrated that the cis isomer of UCA can alter a number of immunological phenomena (5,(7)(8)(9)(10). The exact mechanism of action of UCA, however, has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…a.y-UCA is derived by UV irradiation from trans-\JC\, a natural skin component, and has only recently been implicated in the immunosuppressive action of UV radiation (UVR). De Fabo and Noonan first suggested that UCA was the unique photoreceptor in skin (6), and further recent publications have elucidated its role in immunosuppression (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%